From Collocation to Cultural Perspectives on Polygamy: The Study of Semantic Prosody of Poligami in Ayat-Ayat Cinta 1 and Catatan Hati Seorang Istri 1 - Hsiu-Ying Liu; Layli Hamida; Sheila Wijayanti (PAROLE: Journal of Linguistics and Education, 2020)
This paper studies word collocation of “poligami” in two Indonesian novels entitled Ayat-Ayat Cinta 1 and Catatan Hati Seorang Istri 1, aiming to examine cultural perspectives about polygamy in literary works. Corpus data is used as the basis of studies to examine the collocation of the word “poligami” in the two novels. The results obtained are further classified into nouns, verbs, and adjectives using the language theory involving semantic prosody and culture linguistics. Based on the collocations of “poligami”, the two novelists appear to have different attitudes towards polygamy. The neutral attitude in Ayat-Ayat Cinta 1 indicates that the male author is not exactly in favor of polygamy while Catatan Hati Seorang Istri 1 written by a female author is positive and this reflects women’s acceptance of the idea of polygamy in the novel.